The Role of SARS-CoV-2 Vaccine in Inducing S1-RBD anti-spike IgG Antibody, IL-10, and IL-1β Responses - Mustafa Abdulkareem Salman; Ali S. Mahmoud Al-saadi; Ahlam Kadhum Abd (Diyala Journal of Medicine, 2025)
Background: The Pfizer-BioNTech vaccine has revolutionized the field of vaccines with its approach to eliciting and modulating the immune response against SARS-CoV-2, despite uncertainty about the duration of this response. Objectives: The study aims to estimate the immunological effectiveness of the Pfizer-BioNTech vaccine in eliciting anti-spike IgG antibodies and in modulating IL-10 and IL-1β. Patients and Methods: The Prospective Cohort study was conducted between June 2022 and August 2023 and included 90 participants who had not previously been infected with SARS-CoV-2 and were unvaccinated (16 male and 74 female). Their ages ranged from 19 to 23 years. They were divided into two groups: 45 participants in the control group and 45 participants who received two doses of the Pfizer-BioNTech mRNA vaccine. The levels of S1-RBD (S1 subunit contains a receptor-binding domain) anti-spike IgG antibody, IL-10, and IL-1β were measured in the baseline group and the vaccinated group at 1 and 4 months after the 2nd dose of vaccination using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: The male-to-female ratio was 18:82, with a mean age of 21 among vaccinated student participants. The levels of S1-RBD anti-spike IgG antibody, IL-10, and IL-1β before and post the 2nd dose of the vaccine at 1–4 months were (nonparametric). In addition, the Mann‒Whitney test revealed a significant difference (P< 0.001) in S1-RBD anti-spike IgG antibody and IL-10, IL-1β levels between 1 and 4 months after the 2nd dose of vaccination. Conclusion: The Pfizer-BioNTech vaccine induced robust immune responses, with significant increases in S1-RBD anti-spike IgG antibody levels and in IL-10 and IL-1β levels post-vaccination. Keywords: Pfizer-BioNTech vaccine, S1-RBD anti-spike IgG antibody, IL-10, IL-1β, Vaccination.